Integrating Canva And Similar Digital Design Tools In English Language Teaching: A Literature Review - Saraswati, Ni Putu Ritra Trees Ari Kartika Hadi; Lastari, Ni Kadek Herna; Asnadi, ⁠I Wayan Sumerta Winaya (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study discusses the integration of Canva and similar digital design tools in English Language Teaching (ELT). It synthesizes research on design-based learning, digital storytelling, and the use of visual aids in English as a Foreign Language (EFL) classrooms, highlighting the pedagogical benefits and challenges of employing these technologies. The review emphasizes Canva’s role in enhancing student engagement, creativity, and language skills through interactive and collaborative learning environments. Methodologically, this study conducts a comprehensive synthesis of recent empirical studies, theoretical frameworks, and practical applications related to digital design tools in ELT. The findings underscore the transformative potential of Canva and comparable platforms in fostering learner autonomy, motivation, and 21st-century skills, while also addressing technological and pedagogical challenges. This review contributes to the growing body of knowledge on educational technology integration in language teaching and offers recommendations for educators and researchers.